Comorbidities Associated With Attention-Deficit/Hyperactivity Disorder in Children and Adolescents at a Tertiary Care Setting - Jigar Jogia BSc, PhD; Alia H. Sharif BSc (cand.); Faisal A. Nawaz MBBS (cand.); Abdul Rahman Khan MBBS (cand.); Raed H. Alawami MBBS; Maryam A. Aljanahi BSc; Meshal A. Sultan MBBS, FRCPC (SAGE Publishing, 2022)
Studies have revealed high rates of neurodevelopmental and psychiatric comorbid conditions among individuals diagnosed with attention-deficit/hyperactivity disorder (ADHD). However, research on this topic in the Arab world has been limited. This study evaluates the medical, neurodevelopmental, and psychiatric comorbidities in children and adolescents diagnosed with ADHD in Dubai, United Arab Emirates (UAE). A total of 428 pediatric patients diagnosed with ADHD were included. Children and adolescents with ADHD had high rates of comorbid disorders. Twenty comorbid conditions were identified. More than 3 quarters of the study sample had at least 1 comorbid disorder. The most common comorbidity among children was autism spectrum disorder, and among adolescents was anxiety disorders. Comprehensive assessments are highly warranted to identify and manage associated comorbid conditions. Further research is needed in exploring the biopsychosocial factors contributing to the elevated rate of comorbidity in children and adolescents with ADHD.